Evaluating the Efficiency of the Health Systems of Countries With High and Medium Health Expenditure to Control the Corona Pandemic by Applying to the Kingdom of Saudi Arabia - Mohammed , Abdul Rahman Hassan Hassan (The Arab Journal of Administration, 2024)
The study aimed to measure the efficiency of the health systems performance of countries with high and medium health expenditure to control the Corona pandemic by applying it to the Kingdom of Saudi Arabia. This is done by measuring the relative efficiency using the Data Envelope Analysis (DEA) method. The health expenditure, the number of nurses, the number of doctors, the number of health practitioners, the number of hospital beds were used as inputs to the model, and the percentage of people recovering from corona disease and the number of deaths as outputs of the model. The study sample included 63 countries with high and medium health spending, and the general results of the study were: that there are 14 health systems with 100% efficiency, 4 of them are from high spending countries and 10 are from medium spending countries in both the input and output orientation of the analysis The data envelope, and the Kingdom of Saudi Arabia has achieved superiority over 18 advanced health systems, including reputable countries such as America, Germany and Japan, and the study recommended that high health expenditure is not the only way to achieve the efficiency of controlling the outbreak of the Corona pandemic and the use of accurate scientific studies to apply it effectively as Data Envelope Analysis (DEA).